Topology optimization of planar frames under seismic loads induced by actual and artificial earthquake records. (15th May 2016) - Allahdadian, S.; Boroomand, B.
Highlights: Topology optimization of structures under an earthquake record using SIMP. Design of an artificial record from the actual one for topology optimization. Studies on the performance of various displacement norms as objective function. Comparing sequential node based design with element based design using filtering. Abstract: In this paper, layout optimization of structures under seismic loads is investigated. The difficulties faced in using actual earthquake records in the optimization process are addressed and some methods are proposed to deal with them. The objective is to minimize a suitable norm of displacements of the structure. Since the procedure is extremely time-consuming, along with using the actual record, an artificial record, created by employing basic concepts in earthquake engineering, is used for the optimization process. A series of Gaussian wave packet functions are used to fit the frequency content of the new artificial record to that of the actual one. The parameters obtained are reported for further studies. The well-known Solid Isotropic Material with Penalization (SIMP) method is employed and it is demonstrated that clear layouts may be found through an approach recently proposed by the authors based on the use of a nodal based interpolation of the design variables followed by a sequence of design mesh refining. The results of some numerical experiments are presented for a number of sample problems to show the effectiveness of the procedure proposed.